2013
DOI: 10.3171/2013.3.focus1373
|View full text |Cite
|
Sign up to set email alerts
|

Stereoelectroencephalography for continuous two-dimensional cursor control in a brain-machine interface

Abstract: Stereoelectroencephalography (SEEG) is becoming more prevalent as a planning tool for surgical treatment of intractable epilepsy. Stereoelectroencephalography uses long, thin, cylindrical “depth” electrodes containing multiple recording contacts along each electrode's length. Each lead is inserted into the brain percutaneously. The advantage of SEEG is that the electrodes can easily target deeper brain structures that are inaccessible with subdural grid electrodes, and SEEG does not require a craniotom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…These systems record electric field potentials from cortical populations within the brain parenchyma itself which includes cortex or deeper brain structures. Similar to ECoG, they access a broad frequency spectrum of dynamical brain activity and can be both output and input BCIs (Wang et al, 2010;Vadera et al, 2013;Li et al, 2017). Current and near-term applications of LFP BCI systems are clinical and research oriented.…”
Section: Local Field Potentials (Lfp) Bci Systemsmentioning
confidence: 99%
“…These systems record electric field potentials from cortical populations within the brain parenchyma itself which includes cortex or deeper brain structures. Similar to ECoG, they access a broad frequency spectrum of dynamical brain activity and can be both output and input BCIs (Wang et al, 2010;Vadera et al, 2013;Li et al, 2017). Current and near-term applications of LFP BCI systems are clinical and research oriented.…”
Section: Local Field Potentials (Lfp) Bci Systemsmentioning
confidence: 99%
“…20 Improved access to the epileptogenic network with 3D electrodes implanted using SEEG methodology, when generalized to other functional networks in the brain, may also have broad ramifications for the future development of brainmachine interfaces. 33 For these reasons, it is evident that the SEEG methodology will serve as an important foundation for ongoing clinical treatment and basic science research into brain networks and the spatiotemporal activity therein, in both physiological and pathological stages.…”
Section: Future Directions For Seegmentioning
confidence: 99%
“…A number of studies have demonstrated decoding of motor signals for BCI using sEEG. Vadera et al (2013) demonstrate two-dimensional cursor control from depth electrodes implanted in hand and foot cortical areas. While imagined movements were not investigated, this study highlights one of the advantages of sEEG -the opportunity to record foot cortical areas that reside in the longitudinal fissure that cannot be attained with surface measurements.…”
Section: Motor Bcimentioning
confidence: 99%